Validation of an ensemble modelling system for climate projections for the northwest European shelf seas. (November 2015) - Tinker, Jonathan; Lowe, Jason; Holt, Jason; Pardaens, Anne; Wiltshire, Andy
Highlights: A modelling system to downscales GCM climate projections for shelf seas is presented. Large-scale climate uncertainty is addressed with a Perturbed Physics Ensemble. Simulated mean climate, and high- and low- frequency variability is evaluated. Observations are compared to the modelled distribution of the mean climate. The modelling system is considered suitable as the basis of climate projections. Abstract: The aim of this study was to evaluate the performance of a modelling system used to represent the northwest European shelf seas. Variants of the coupled atmosphere–ocean global climate model, HadCM3, were run under conditions of historically varying concentrations of greenhouse gases and other radiatively active constituents. The atmospheric simulation for the shelf sea region and its surrounds was downscaled to finer spatial scales using a regional climate model (HadRM3); these simulations were then used to drive a river routing scheme (TRIP). Together, these provide the atmospheric, oceanic and riverine boundary conditions to drive the shelf seas model POLCOMS. Additionally, a shelf seas simulation was driven by the ERA-40 reanalysis in place of HadCM3. We compared the modelling systems output against a sea surface temperature satellite analysis product, a quality controlled ocean profile dataset and values of volume transport through particular ocean sections from the literature. In addition to assessing model drift with a pre-industrial control simulation the modelling system was evaluated against observations and the reanalysis driven simulation. We concluded that the modelling system provided an excellent (good) representation of the spatial patterns of temperature (salinity). It provided a good representation of the mean temperature climate, and a sufficient representation of the mean salinity and water column structure climate. The representation of the interannual variability was sufficient, while the overall shelf-wide circulation was qualitatively good. From this wide range of metrics we judged the modelling system fit for the purpose of providing centennial climate projections for the northwest European shelf seas.